How alternative landscapes in the boreal forest impact woodland caribou using a model of animal movement, perception and memory - Collis, Brianna (University of Guelph, 2018)
The boreal ecotype of woodland caribou, Rangifer tarandus caribou, is a threatened species in Canada. Their decline is complex, but cumulative effects of anthropogenic activity - including habitat alteration and loss from economic activities - are implicated. This study investigates how a projection of current trends impacts caribou using alternative landscapes in northern Ontario. Landscapes are compared with an empirically-parameterized individual-based movement model to identify how landscape change impacts boreal woodland caribou. Results indicate that a business- as-usual landscape will continue to negatively impact woodland caribou persistence and population growth, as well as affect how caribou use the landscape with respect to movement and landcover occupation. Neither the existing landscape nor a business- as-usual projection stopped caribou decline, and caribou searched more-disturbed landcover types in the business-as-usual landscape. Results have implications for species conservation, landscape planning, boreal land-use practices, spatial ecology, and applied landscape ecology’s role in the recovery of imperilled species.